Readiness to care and factors influencing readiness to care for patients in the intensive care units among novice nurses - Suveksha Giri; Melita Sheilini; Prima Jenevive Jyothi D'Souza (Elsevier, 2022)
Problem considered: Nurses are the heart and soul of any healthcare institution. A skilled, qualified nurse with the readiness to care for patients in critical care setting is the dire need for today's world. Methods: A cross-sectional descriptive survey was conducted among novice nurses working in the selected tertiary care hospitals to assess the readiness to care for patients in the intensive care unit (ICU) and the factors influencing readiness to care. The sample were selected using purposive sampling technique. Results: The majority 157 (52.4%) had moderate readiness, 143 (47.6%) novice nurses had high readiness to care for patients in ICUs. The top six factors expressed by the participants were: knowledge of the fundamental subjects 292(97.3%), continuing nursing education 278(92.7%), feedback by peers and superiors 283(94.3%), internal motivation 277(93.3%), communication skills 277(92.3%), and proper documentation of care given 278(92.7%). There was a statistically significant association between readiness to care and gender (χ2 = 9.060; p = .011), area of work (χ2 = 10.009; p = .040), duration of clinical exposure in ICUs during the course of study (χ2 = 18.301; p = .011), duration of clinical experience during final year of training (χ2 = 10.315; p = .016), specific ICU related training (χ2 = 6.511; p = .011), and duration of induction programme (χ2 = 50.23; p= <.001) Conclusion: The novice nurses had moderate readiness to practice in ICUs. The nursing educational sector and the nursing service sector can devise certain structures which can help increase the readiness of novice nurses to work in ICUs by focusing on the factors identified.